Merebut Tafsiran Otoritatif Keagamaan; Perdebatan dan Kontroversi Prosesi Hukuman Ta’zir Cambuk di Lapas Aceh - Yahya, Faisal; Mubarrak, Husni; Harjoni; Ridha, Muhammad; Kafei Kjoor, Amir Muhammed (State of Islamic Institute Langsa, 2024)
This article discusses the debates and controversies surrounding the authoritative interpretation of Sharia law regarding the caning punishment process in correctional facilities (prisons) in Aceh, which was previously conducted in open fields. The debate emerged and took place across various media platforms, including social media, following the issuance of the Aceh Governor's Regulation in 2018 concerning the relocation of the punishment process. The discussion extended to deliberating the most legitimate interpretation regarding the necessity for the caning punishment to be witnessed by a group of believers; the selection of the location where the punishment is carried out; and the intent and purpose of the caning punishment itself to be witnessed by the public, as explicitly stated in Q.S. An-Nur: 2. Using literature study as the research method, this article concludes that there has been a shift in religious interpretation towards authoritarianism by considering and asserting certain interpretations as authoritative and